Navy Bean and Rice Bran Intake Alters the Plasma Metabolome of Children at Risk for Cardiovascular Disease - Li, Katherine J.; Borresen, Erica C.; Jenkins-Puccetti, NaNet; Luckasen, Gary; Ryan, Elizabeth P. (Frontiers in Nutrition, 2018)
Abnormal cholesterol in childhood predicts cardiovascular disease (CVD) risk in adulthood. Navy beans and rice bran have demonstrated efficacy in regulating blood lipids in adults and children; however, their effects on modulating the child plasma metabolome has not been investigated and warrants investigation. A pilot, randomized-controlled, clinical trial was conducted in 38 children (10 ± 0.8 years old) with abnormal cholesterol. Participants consumed a snack for 4 weeks containing either: no navy bean or rice bran (control); 17.5 g/day cooked navy bean powder; 15 g/day heat-stabilized rice bran, or; 9 g/day navy beans and 8 g/day rice bran. Plasma metabolites were extracted using 80% methanol for global, non-targeted metabolic profiling via ultra-high performance liquid-chromatography tandem mass spectrometry. Differences in plasma metabolite levels after 4 weeks of dietary intervention compared to control and baseline were analyzed using analysis of variance and Welch’s t-tests (p≤0.05). Navy bean and/or rice bran consumption influenced 71 plasma compounds compared to control (p≤0.05), with lipids representing 46% of the total plasma metabolome. Significant changes determined for 18 plasma lipids in the navy bean group and 10 plasma lipids for the rice bran group compared to control, and 48 lipids in the navy bean group and 40 in the rice bran group compared to baseline, support the hypothesis that consumption of these foods impact blood lipid metabolism with implications for reducing CVD risk in children. Complementary and distinct lipid pathways were affected by the diet groups, including acylcarnitines and lysolipids (navy bean), sphingolipids (rice bran), and phospholipids (navy bean + rice bran). Navy bean consumption decreased free fatty acids associated with metabolic diseases (palmitate and arachidonate) and increased the relative abundance of endogenous anti-inflammatory lipids (endocannabinoids, N-linoleoylglycine, 12,13-diHOME). Several diet-derived amino acids, phytochemicals, and cofactors/vitamins with cardioprotective properties were increased compared to control and/or baseline, including 6-oxopiperidine-2-carboxylate (1.87-fold), N-methylpipecolate (1.89-fold), trigonelline (4.44- to 7.75-fold), S-methylcysteine (2.12-fold) (navy bean), salicylate (2.74-fold), and pyridoxal (3.35- to 3.96-fold) (rice bran). Findings from this pilot study support the need for investigating the effects of these foods for longer durations to reduce CVD risk. Trial registration: clinicaltrails.gov (identifier NCT01911390).